Contabilidade nacional: análise da economia brasileira sob as óticas da despesa e da renda, no período 1990-2000 - Santos, Rogério Frota Leitão dos (2002)
The present dissertation has as its main goal the analysis of the trajectory of the main macroeconomic variables of the Brazilian economy during the Plano Real, more precisely in the period that goes from 1990 to 2000, using information from the national accounts. ln this study, Gross Domestic Product (GDP) accounts are analyzed in terms of income and expenditure. Besides that, an investment multiplier is calculated to illustrate on how much the Gross Formation of Capital (GFB) contributes to raise Brazilian GDP, which has revealed to be ofthe order of 1.69. However, in virtue ofthe volume ofGFB having been around 20% of the GDP and due to investment having been directed mainly to the services sector, the national economy was not able to enhance productive sectors that favor a raise of Brazilian exports, with a consequent slowdown of its growth rate in the decade